Moten in Canterbury Tales: The speaker’s expression of the self - Stadnik, Katarzyna (Studia Anglica Posnaniensia, 2012)
In the paper, we posit the centrality of the speaker in language. In so doing, we refer to the fact that language users may select particular linguistic expressions to encode their understanding of a given situation. This observation alludes to the concept of subjectivity in linguistics, and evokes the notion of modality, concerned, broadly speaking, with the speaker's attitude to the proposition. In English, linguistic devices used to signal the varying degrees of the speaker's commitment towards the proposition include modal verbs. Historically, they can be claimed to have developed from less to more subjective meanings, as in the case of the modal verb must. Its epistemic meaning is believed to have evolved from its deontic sense in the Middle English (ME) period. While some authors argue that, at this stage of its development, epistemic must was less, rather than more subjective, we test a different supposition. In our view, epistemic must occurring in generalized necessity statements might acquire a more subjective reading. Specifically, it seems possible to argue that, by personalizing generalized truths, the speaker tinges them with more subjective overtones. We exemplify the claim using the occurrences of ME *moten ‘must’ in Canterbury Tales.